Critical aspects of biomass ashes utilization in soils: composition, leachability, PAH and PCDD/F - Freire, Márcia
Bottom and fly ashes streams collected along a year in several biomass thermal plants were studied. The bulk composition of ashes and other chemical characteristics that may impact soil application showed a high variability depending on the ash stream, combustion technology and ash management practice at the power plants. The acid neutralization capacity (ANC) and metal’s availability for leaching at fixed pH 7 and 4 was performed according with EA NEN 7371, as a quick evaluation method to provide information on the long-term behavior of ashes, regarding heavy metals and also plant nutrients release. Also the pH dependence leachability study was performed according to CEN/TS 14429 for predicting the leaching behavior under different scenarios. Leachability profiles were established between pH 3 and 12, allowing to distinguish different solubility control phenomena of toxic heavy metals (Cu, Cr, Mn, Ni, Zn, Pb) as well as other salts (Ca, K, Mg, Na, Cl). The ANC of fly ashes at pH 4 (3.6–9.6 molH+/kg) were higher than that observed for the bottom ashes (1.2–2.1 molH+/kg). Ashes were also characterized for persistent organic pollutants (POP), such as polycyclic aromatic hydrocarbons (PAH) and paradibenzodioxines and furanes (PCDD/F). Contents were found to be much higher in fly ash than in bottom ash streams. None of the PAH levels did reach the current national limit value of sewage sludge application in soils or the guide value for ash in north European countries. However, PCDD/F contents, which are not regulated, varied from non-detectable levels to high amounts, regardless the level of loss on ignition (LOI) or unburned carbon content in fly ashes. Given the current ash management practices and possible use of blends of bottom and fly ash streams as soil conditioners resembles clear the urgent need to regulate ash utilization in soils, incorporating limit values both for heavy metals, PAH and PCDD/F.